Civilizations of the Silk Road - Chang, H. K., 1940- (New York : Routledge, 2023)
"This book describes the interactions between various civilizations and societies along the Silk Road between 500 BCE and 1500 CE, the period from the first encounters of ancient Greek and Persian civilizations to the time when maritime exchanges between Europe and Asia exceeded those on land. Starting with the genesis and features of different civilizations, the book focuses on the history and exchange of different cultures along the Silk Road: Zhang Qian's successful pioneering feats which inaugurated the opening stretch of the Silk Road, the origins and dissemination of Zoroastrianism, Buddhism, Christianity, Manichaeism, Nestorian-Christianity and Islam; the westward spread of papermaking and printing; as well as long-distance exchanges of scripts and spoken language, music, architecture, painting, and sculpture. It also outlines the historically significant migrations of various peoples from east to west, such as the Xiongnu, Yuezhi, Han, Qiang, Hephthalites, Turkic groups, Uighurs, Mongols, and Xibe. The author has interwoven facts, anecdotes and his own experiences of study throughout the book, making it an interesting history reader and cultural primer. This book thus will be an essential read to students and scholars of Eurasian Studies, Chinese History and those who are interested in the history of the Silk Road in general"--
Preface -- Chapter I "Civilization": origins, diversity & continuity -- Chapter II Alexander's Eastern campaigns, Hellenism & Gandharan art -- Chapter III Mysteries of the Western regions: pioneering Zhang Qian & Han dynasty explorers -- Chapter IV Buddhism's genesis: to the West is a deity, Buddha is his name -- Chapter V Buddhism's spread in China: contemporaries Kumarajiva and Faxian: the encounter that didn't happen -- Chapter VI Sogdians along the Silk Road -- Chapter VII Golden peaches of Samarkand -- Chapter VIII Silk & paper -- Chapter IX Printing migrates West, alphabets migrate East -- Chapter X Origins and spread of Islamic civilization -- Chapter XI Islam in China -- Chapter XII Rise of the Turkic-speaking peoples and their westward migration -- Chapter XIII Westward migration of the Turkic peoples: from the Syr Darya to the Danube -- Chapter XIV Eurasia under Mongol rule -- Chapter XV The Timurid empire & the Ming treasure voyages -- Bibliography -- Index.
Keywords: Silk Road -- Civilization; Eurasia -- Civilization; China -- Civilization; Asia, Central -- Civilization; HISTORY / Ancient / General; HISTORY / Asia / General; HISTORY / Asia / China